Dinamika Judicial Review oleh Mahkamah Konstitusi: Merumuskan Ulang Kewenangan Pengujian Peraturan Perundang-Undangan - Erham Erham; Urwatul Wutsqah (Jurnal Hukum Lex Generalis, 2026)
This research examines the urgency of reformulating the judicial review authority in Indonesia, which is currently divided between the Constitutional Court (reviewing Laws against the Constitution) and the Supreme Court (reviewing regulations below Laws against Laws). This bipartite system, or dualism of judicial review, is found to trigger inconsistent rulings, divergent legal interpretations, and legal uncertainty due to the separation of legality and constitutionality aspects. The study recommends the integration of judicial review authority into a unified judicial review system under the Constitutional Court. This integration aims to create linear legal harmonization and ensure that the entire hierarchy of legal norms aligns strictly with the principles of a democratic constitutional state.